Case Report: Lateral Habenula Deep Brain Stimulation for Treatment-Resistant Depression - Wang, Zhiyan; Cai, Xiaodong; Qiu, Rirang; Yao, Chen; Tian, Ye; Gong, Chen; Zhang, Yingli; Xu, Bin; Zhang, Doudou; Zang, Yu; Liu, Jiali; Peng, Bo; et al. (Frontiers in Psychiatry, 2021)
Treatment-resistant depression (TRD) is a chronic and severe psychiatric illness associated with limited therapeutic options. Deep brain stimulation (DBS) is currently a promising therapy for those TRD patients. However, the efficacy, safety and its therapeutic mechanisms are still unclear. Here we reported A TRD patient with failure to medical, psychological, electroconvulsive as well as ketamine treatments chosen the lateral habenula (LHb) DBS to improve his clinical symptoms. The advanced electrodes are implanted into bilateral LHb, which are compatible with magnetic resonance imaging and could collect local field potentials (LFPs). The patient showed acute stimulation effects and achieved long-term improvements in his depression, anxiety and sleep with high frequency stimulation, accompaning increase in its LFPs. These results provided clinical evidence in safety and efficacy and electrophysiological basis of LHb DBS for TRD.